Effects of glucagon-like peptide-1 receptor agonists on mortality and cardiovascular events: A comprehensive meta-analysis of randomized controlled trials. (1st August 2017) - Monami, Matteo; Zannoni, Stefania; Pala, Laura; Silverii, Antonio; Andreozzi, Francesco; Sesti, Giorgio; Mannucci, Edoardo
Abstract: Introduction: The publication of the results of LEADER and SUSTAIN-6 trials suggested a possible beneficial effect of the class of GLP-1 receptor agonists on cardiovascular morbidity and mortality. The aim of the present meta-analysis is to collect and synthetize all available evidence on the effect of GLP-1 receptor agonists on cardiovascular events and mortality. Methods: A Medline search for GLP-1 receptor agonists (exenatide, liraglutide, lixisenatide, albiglutide, dulaglutide, or semaglutide) was performed, collecting all randomized clinical trials with a duration > 11 weeks, enrolling patients with type 2 diabetes, and comparing a GLP-1 receptor agonist with placebo or any other non-GLP-1 receptor agonist drug. The principal outcome of this analysis was the effect of GLP-1 receptor agonists on all-cause and cardiovascular mortality, overall (fatal plus nonfatal) myocardial infarction, stroke, and heart failure. Results: Out of 113 trials fulfilling inclusion criteria (mean duration 41.7 ± 38.2 weeks), 32, 25, 48, 43 and 32 reported at least one event for all-cause and cardiovascular mortality, overall (fatal plus nonfatal) myocardial infarction, stroke, and heart failure, respectively. In GLP-1 receptor agonist-treated patients, all-cause mortality, cardiovascular mortality, and myocardial infarction were significantly lower than in comparators (MH-OR [95% CI] 0.88 [0.79–0.97], p  = 0.015, 0.84 [0.74–0.96], p  = 0.009, and 0.90 [0.80–1.00], p  = 0.050, respectively), whereas no beneficial effect was observed for stroke and heart failure (MH-OR [95% CI] 0.90 [0.81–1.00]. p  = 0.059. 0.89 [0.76–1.04]. p  = 0.15. and 0.92 [0.81–1.06]. p  = 0.25. respectively). Conclusions: Overall, the agents of this class appear to reduce all-cause mortality, cardiovascular mortality, and the incidence of myocardial infarction at mid-term follow up.